Seismic slip history of the Pizzalto fault (central Apennines, Italy) using in situ‐produced 36Cl cosmic ray exposure dating and rare earth element concentrations. Issue 3 (31st March 2016) - Tesson, J.; Pace, B.; Benedetti, L.; Visini, F.; Delli Rocioli, M.; Arnold, M.; Aumaître, G.; Bourlès, D. L.; Keddadouche, K.
Abstract: Morphological and geological observations reveal that most Apenninic faults are highly segmented and that the majority of the fault segments are less than 10 km long. Although these faults have undergone numerous paleoseismological investigations, quantitative data remain crucially lacking for a large number of fault segments. Because such data are essential to understanding how these faults have ruptured and interacted in the past and how they might behave in the future, we investigated the Holocene seismic history of the Pizzalto normal fault, a 13 km long fault segment belonging to the Pizzalto‐Rotella‐Aremogna fault system in the Apennines. We collected 44 samples from the Pizzalto fault plane exhumed during the Holocene and analyzed the 36 Cl and rare earth element (REE) contents. Together, the 36 Cl and REE concentrations show that at least six events have exhumed 4.4 m of the fault scarp between 3 and 1 ka, with slip per event values ranging from 0.3 to 1.2 m. No major events have been detected over the last 1 kyr. The Rotella‐Aremogna‐Pizzalto fault system has a clustered earthquake behavior with a mean recurrence time of 1.2 kyr and a low to moderate probability (ranging from 4% to 26%) of earthquake occurrence over the next 50 years. Key Points: At least six earthquake events over the last 3 kyr have ruptured the Pizzalto fault Rare earth elements can be used to recover past events on a fault plane Earthquakes rupturing the Rotella‐Aremogna fault system are clustered in time